Toward Advanced High-k and Electrode Thin Films for DRAM Capacitors via Atomic Layer Deposition - Kim, Se Eun; Sung, Ju Young; Jeon, Jae Deock; Jang, Seo Young; Lee, Hye Min; Moon, Sang Mo; Kang, Jun Goo; Lim, Han Jin; Jung, Hyung Suk; Lee, Sang Woon (Advanced Materials Technologies, 2023)
Dynamic random access memories (DRAMs) are currently used as the core memory in computing systems because of their high speed and density. Their demand should continue to grow owing to increased data usage. A unit cell in a DRAM consists of one transistor and one capacitor, and the data are stored in the capacitor. As the size of the unit cell decreases to improve the memory density by aggressive scaling, it is important to secure sufficient capacitance in the capacitor. In this regard, technological advances in the fabrication of capacitors are of great importance; accordingly, the materials and processing of high-k thin films require developmental innovations. Besides, it is necessary to develop electrode materials that optimize the function of high-k thin films. In this review, recent advances in achieving sufficient capacitance in DRAM capacitors are summarized from structural and material/process perspectives, and the future direction of DRAM capacitor development is discussed. Atomic layer deposition (ALD) is a key technique that enables the growth of functional thin films for DRAM capacitors; thus, recent advances in the deposition of high-k and electrode thin films grown using the ALD technique are addressed.
Keywords: Aggressive scaling; Atomic-layer deposition; Computing system; Data usage; Dynamic random access memory; High Speed; High- k; Memory density; Thin-films; Unit cells; atomic layer deposition; capacitors; dynamic random access memory; electrodes; high-k; thin films